2015
DOI: 10.1007/s11745-015-4058-0
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Unsaturated Fatty Acids on Palmitic Acid‐Induced Toxicity in Skeletal Muscle Cells is not Mediated by PPARδ Activation

Abstract: Unsaturated free fatty acids (FFA) are able to prevent deleterious effects of saturated FFA in skeletal muscle cells although the mechanisms involved are still not completely understood. FFA act as endogenous ligands of peroxisome proliferator-activated receptors (PPAR), transcription factors regulating the expression of genes involved in lipid metabolism. The aim of this study was to determine whether activation of PPARδ, the most common PPAR subtype in skeletal muscle, plays a role in mediating the protectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
(61 reference statements)
0
14
0
Order By: Relevance
“…18 Maternal adiposity is strongly associated with an increased risk of essentially all maternal and fetal complications. [20][21][22] However, to our knowledge, our study is the first to in- Oxidative stress can be defined as an imbalance between free radical generation and antioxidant defense and is recognized as a key factor in the pathogenesis of adverse pregnancy outcomes. 19. Previous studies have shown that PA induces cytotoxicity in a diverse set of cells including trophoblasts, skeletal muscle, and liver cells.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…18 Maternal adiposity is strongly associated with an increased risk of essentially all maternal and fetal complications. [20][21][22] However, to our knowledge, our study is the first to in- Oxidative stress can be defined as an imbalance between free radical generation and antioxidant defense and is recognized as a key factor in the pathogenesis of adverse pregnancy outcomes. 19. Previous studies have shown that PA induces cytotoxicity in a diverse set of cells including trophoblasts, skeletal muscle, and liver cells.…”
Section: Discussionmentioning
confidence: 88%
“…19. Previous studies have shown that PA induces cytotoxicity in a diverse set of cells including trophoblasts, skeletal muscle, and liver cells. [20][21][22] However, to our knowledge, our study is the first to in- Oxidative stress can be defined as an imbalance between free radical generation and antioxidant defense and is recognized as a key factor in the pathogenesis of adverse pregnancy outcomes. 25 Although OS is a common feature of normal pregnancy, persistent, overwhelming OS leads to the consumption and decline of antioxidants, affecting placental antioxidant capacity and reducing systems.…”
Section: Discussionmentioning
confidence: 88%
“…The highest expression level of PPARD mRNA is observed in Sertoli cells, intestine, heart, liver, brain and kidney tissues [ 2 , 3 , 4 , 5 ]. The most popular ligands of PPARβ/δ are: unsaturated fatty free acid (FFA) and their metabolites [ 1 , 2 , 5 , 6 ], GW0742 [ 7 , 8 , 9 ], ezetimibe [ 7 ], GW501516 [ 6 , 10 ], 15-HETE, 4-HNE, 4-HDDE and ATRA [ 2 ]. The PPAR activation plays a vital role in regulation of many physiological and pathological processes, such as energy consumption, inflammation, tissue repair, proliferation and differentiation of various types of cells [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The PPARβ/δ receptor exerts a pleiotropic impact on skeletal muscle physiology and metabolism. The use of cell cultures and animal models has revealed that PPARβ/δ activation results in a metabolic shift promoting lipid utilization (increased fatty acid uptake and oxidation) and reduced carbohydrate oxidation [ 6 , 11 , 13 ]. These modifications occur through upregulation of the expression of proteins implicated in myocyte energetic substrate preference, such as fat tissue (FAT)/CD36 [ 13 , 14 ], lipoprotein lipase, PDK4 or CPT1 [ 2 , 4 , 6 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation